PENYELESAIAN KREDIT MACET DENGAN JAMINAN HAK TANGGUNGAN PADA PT BANK DANAMON INDONESIA, Tbk UNIT PASAR BANDAR JAYA LAMPUNG TENGAH - , Arsyasepta Prawidika, Taufiq El Rahman, S.H., M.Hum ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study is purposed to find out the reasons of PT. Bank Danamon Indonesia Tbk Unit Pasar Bandar Jaya Lampung Tengah in collateral binding of immovable objects with the deed of mortgage right (APHT) for earning credits which should be enough with on the power letter of mortgage right impose (SKMHT) and to understand the legal protection which is obtained by PT. Bank Danamon Indonesia Tbk Unit Pasar Bandar Jaya Lampung Tengah in the repreship with the auction of execution of the mortgage right objects through Kantor Pelayanan Kekayaan Negara dan Lelang (KPKNL). This study is an empirical legal research. The sampling techniques use nonprobability sampling techniques with sampling which is conducted by purposive sampling. The data is obtained through library research as well as obtained data through field research which is analyzed qualitatively and written with descriptive methods. The results and discussion conclude that on the power letter of mortgage right impose (SKMHT) will give a legal force to the position of creditor as a preferred creditor if it has been acted upon by making of the deed of mortgage right (APHT). The repreship is carried out by way of the execution of mortgage right collateral objects with the auction through Kantor Pelayanan Kekayaan Negara dan Lelang (KPKNL). The law protection which is obtained under article 6 of mortgage right law provides that if the debtor is default then the first holder of mortgage right has the right to sell mortgage right objects on the power itself through a public auction and take repayment of credits from the sale. The auction can realize optimal prices because the auction system is open thus the goods will be sold with the optimal price for the repayment of credits.